2021
DOI: 10.2399/yod.20.640377
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Gender Course on the Gender Attitudes, Critical Thinking Dispositions, and Media Literacy Skills of University Students

Abstract: This study aims to determine the effect of a university elective course focusing on gender on students' gender attitudes, critical thinking dispositions, and media literacy skills. The research design was quasi-experimental, and the study was conducted with a pretest/posttest control group. The sample of the study consisted of 74 students who took a course on gender during the fall semester of the 2016-2017 academic year and 70 students who had similar characteristics but did not receive the course. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…Raising these scores with education is more difficult in this case, so education may not affect gender role attitudes and gender perception. When studies showing the benefits of education are examined from the literature, it is seen that the pretest scores of the students are lower than those in this study (for perception, Uzun et al, 2017;for attitude, Egelioğlu Cetişli et al, 2017;Koç et al, 2021). In this study, the students' high scores in the pretest on the gender-related scales may be because they are university students (Vefikuluç et al, 2007;Yılmaz et al, 2009;Kahraman et al, 2014), come from regions with a relatively higher socioeconomic status (Kul Uçtu and Karahan, 2016), and there are more students from the nuclear family rather than the traditional extended family (Kul Uçtu and Karahan, 2016).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Raising these scores with education is more difficult in this case, so education may not affect gender role attitudes and gender perception. When studies showing the benefits of education are examined from the literature, it is seen that the pretest scores of the students are lower than those in this study (for perception, Uzun et al, 2017;for attitude, Egelioğlu Cetişli et al, 2017;Koç et al, 2021). In this study, the students' high scores in the pretest on the gender-related scales may be because they are university students (Vefikuluç et al, 2007;Yılmaz et al, 2009;Kahraman et al, 2014), come from regions with a relatively higher socioeconomic status (Kul Uçtu and Karahan, 2016), and there are more students from the nuclear family rather than the traditional extended family (Kul Uçtu and Karahan, 2016).…”
Section: Discussioncontrasting
confidence: 48%
“…The results of the study revealed that it was found that the online distance course "Prejudice and Discrimination" did not affect gender roles attitudes and gender perceptions. When the literature was examined, studies showed that education did not affect gender role attitudes (Toraman and Özen, 2019;Karakoç et al, 2022), as well as studies showing that it affected it positively (Uzun et al, 2017;Egelioğlu Cetişli et al, 2017;Erdol and Gözütok, 2019;Koç et al, 2021). Similarly, when looking at the studies examining the effect of education on gender perception, studies showed that education had no effect (Ernst et al, 2000;Karakoç et al, 2022) as well as studies showing that it affected it positively (Seçgin and Kurnaz, 2015;Uzun et al, 2017;Gönenç et al, 2018;).…”
Section: Discussionmentioning
confidence: 99%
“…Al relacionar el pensamiento crítico y la perspectiva de género, las evidencias reportan que las personas con habilidades del pensamiento crítico son capaces de considerar diferentes perspectivas, son respetuosos y tolerantes con otros (Aybek, 2018). Dicho de manera distinta, Li (2022) expone que las personas con sesgo cognitivo aceptan los estereotipos, normas y roles de género sin previa reflexión, ni cuestionamientos críticos, el estado de las cosas, producidos según Koç et al (2021), por la falta de capacidad para evaluar el lenguaje y los comentarios discriminadores presentes en la cotidianidad y comunicacionalmente. Por esto, las habilidades del pensamiento crítico resultan fundamentales para superar los sesgos, estereotipos y roles de género impuestos socioculturalmente (Li, 2022;Liao y Wang, 2020).…”
Section: Habilidades Del Pensamiento Críticounclassified
“…En síntesis, el pensamiento crítico es una herramienta que permite indagar en los sucesos de la vida real (educativos, profesionales, laborales y cotidianos), para su comprensión y trasformación (Alajlan y Aljohani, 2019;Pedraja et al, 2023). A partir de esto, se puede decir que el desarrollo de formas complejas de pensar permite convertir a los estudiantes en pensadores independientes (Alharbi, 2022), los cuales mediante la adquisición de habilidades del pensamiento crítico podrán evaluar el lenguaje y comentarios con sesgos, estereotipos y roles de género que se manifiestan de manera estática y desigual (Koç et al, 2021).…”
Section: Habilidades Del Pensamiento Críticounclassified
See 1 more Smart Citation